Assisting failure‐prone individuals to navigate achievement transitions using a cognitive motivation treatment (attributional retraining). Issue 9 (11th September 2013) - Boese, Gregory D. B.; Stewart, Tara L.; Perry, Raymond P.; Hamm, Jeremy M.
Abstract: Transitions to novel achievement settings are often accompanied by unfamiliar learning conditions and unanticipated failure that undermine how individuals adapt to such situations. For first‐year students, the transition to college is imbued with adverse learning conditions that can result in decreased motivation and academic performance. This study examined the efficacy of a motivation‐enhancing treatment, attributional retraining (AR), to assist students who are at risk because of a high‐failure avoidance orientation (tendency to maintain self‐worth by avoiding failure). For high‐ (but not low) failure avoidance students, AR fostered an adaptive psychological mindset (course grade expectations, judgments of course responsibility) and better academic performance (course grade, grade point average). Findings suggest the utility of AR to offset the negative effects of a high‐failure avoidance self‐worth orientation.